Research on the Advisory Jurisdiction of the International Court of Justice - Qi Li (Studies in Law and Justice, 2023)
The International Court of Justice (ICJ) is a sovereign intergovernmental judicial body of the United Nations for the settlement of international disputes, and the jurisdiction of the ICJ, as one of the main means for the ICJ to exercise criminal jurisdiction, includes both contentious and advisory jurisdiction. Among them, the advisory jurisdiction of the International Court of Justice is far less effective and influential than the contentious jurisdiction, but as a supplement to the contentious jurisdiction, it still has an important influence on the settlement of international disputes in the international field. In order to solve disputes in the international community and give full play to the role of international law, we need to continuously explore the realistic path to improve the advisory jurisdiction system of the ICJ. With our country, we can also promote the guarantee and realization of the advisory jurisdiction of the ICJ and promote the peaceful settlement of international disputes by increasing the degree of participation in the exercise of jurisdiction of the ICJ and playing the responsibility of superpowers.